Differences in ureide and amino acid content of water stressed soybean inoculated with Bradyrhizobium japonicum and B. elkanii - Ramos, Maria Lucrecia Gerosa; Parsons, Richard; Sprent, Janet Irene (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to study the response to water stress of a drought sensitive soybean cultivar inoculated with Bradyrhizobium japonicum (strain CB1809, Semia 586) and B. elkanii (strain 29W, Semia 5019). CB1809 nodulated plants produced a significantly higher root fraction (19%) than 29W (14.6%). Plants inoculated with CB1809 produced less nodules and accumulated more nitrogen than those inoculated with 29W. In general, low amounts of ureides in nodules were found in watered plants inoculated with either CB1809 or 29W strains, but those levels were five-fold increased in stressed plants inoculated with CB1809. Nodules formed by strain CB1809 had aspartate and glutamate as major amino acids, while those formed by 29W had glutamate, asparagine and alanine. In nodules of plants inoculated with CB1809 aspartate showed the highest accumulation (5 mmol g-1); in stressed plants this amino acid reached a value of 26 mmol g-1, and asparagine was not detected. Nodules formed by the strain 29W accumulated 1 mmol g-1 of aspartate, whether plants were stressed or not. Asparagine was the major amino acid found in nodules from watered plants (6 mmol g-1) and the amount of this amino acid was six-fold increased when plants were water stressed.